Pengembangan Sistem Proses Retting Serat Kenaf (Hibiscus cannabinus L.) Menggunakan Kultur Mikrobial Pada Lingkungan Non-Aseptik - Makhmudun Ainuri; Gumbira Said; Mohammad Romli; Sudjindro Sudjindro (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 1997)
Kenaf fibres is one of the primary fibre commodities in Indonesia. However, the national total production of the fibre meets only 20-30% of the national consumption. In addition, most of the fibre quality is still low, where, 15-20 % of the fibre grouped into quality A, 40-50 % quality B and the rest, is grouped into quality C. It is likely that the resting process in the chain of fibre production is the main source of its low quality. n order to reduce rettin time and improve the fibre quality obtained, various efforts have been done to improve the rating processes, including the use of integrated processes of microbiological, mechanical and semi mechanical processes. The addition 2.5 % of adaptive starter of Bacillus polymyxa BCC-27 into 'wiling process was unsignificant (p > 0.05). It is likely that the case was nullified by the addition of 0.005 % urea. The six and three hour per day circulation treatments could enhance the condition of resting processes; mainly pH and temperature, but still less than DO. Without circulation unsignificant (P > 0.005) toward the degradation of peclin, holocellulose, cellulose and lignin. The fibre produced by the sixth combination treatments, that are circulation treatments and 0.05 % urea by culture enrichment 2.5 % meets the standart quality A. End-point rating or top resting accured on the process period of after five day. The process is still under resting on the fifth day, but over 'wiling after the seventh day.